STRATEGI KPU DALAM MENINGKATKAN TINGKAT PARTISIPASI PEMILIH DISABILITAS DI KABUPATEN BOYOLALI - Aris Tri Haryanto, Shinta Dian Wahyuni & (Master of Public Administration, Universitas Slamet Riyadi, 2019)
The purpose of this study is to determine the strategy of Boyolali DistrictElection Commission in increasing the level of disability participation inBoyolali District. The type of research used in this study is qualitativedescriptive. Boyolali District election Commission conducted research.The data used is primary data and secondary data. Data collectiontechniques incloud interviews, observations, and documentation. Dataanalysis techniques using the Intractive model Miles and Huberman. Thevalidity of data in research is used triangulation techniques. Based on theresults of the SWOT analysis, it can be concluded that the strategy ofincreased participation of the by the General Boyolali CommissionerAmong others: 1) institutional strengthening, which is established:increasing the role of electoral Committee of the subdistrict (PPK),Panitia Pemungutan Suara (PPS), and the group voting organizers(KPPS) as a communicator in the socialization of election activities, Theestablishment of democracy Volunteers, 2) socialization strategies, whichare founded: Face to Face Communication, Media communication, andthe election of the Daughters of Democratic disability.Key words: Participation, disability, socialization, communication